Effect of Row Ratio on Growth, Nodulation, Yield and Nutrient Uptake in Maize (Zea mays L.) with Urdbean and Mungbean Intercropping System - Pandey, Vinay; Singh, Adesh; Dwivedi, Ashish; Tomar, S. S.; Naresh, R. K.; Shahi, U. P. (International Journal of Bio-resource and Stress Management, 2016)
A field experiment was conducted during kharif season of 2013 on sandy loam soil at CRC of S.V.P.U.A. & T. Meerut. In this investigation 09 treatment combination viz., maize with normal (1:1), paired (2:2) and strip (3:3) planted urdbean and mungbean along with all the three crops in their sole stands were tested in randomized block design with three replications. The study revealed that strip planted maize+urdbean (3:3) being on par with maize+mungbean (3:3) recorded significantly highest values of plant height, plant spread and dry matter accumulation, yield attributes viz., cob length (cm), grains row-1, grains cob-1 and test weight (g) and yield of maize in terms of biological yield (123.0 q ha-1) however, harvest index was higher under normal (1:1) maize+urdbean. In terms of nitrogen, phosphorus and potassium uptake in grains and stover and their total uptake of each, strip (3:3) planted maize proved its superiority over sole and normal (1:1) planted maize. Likewise in intercrops, all the growth parameters, nodules plant-1, yield attributes, yields, nutrients uptake and their total uptake were statistically superior in their sole as compared to normal (1:1), paired (2:2) and strip (3:3) planting with maize. Therefore, strip planted maize+mungbean/urdbean (3:3) intercropping system proved to be better growth and development, nodulation, biological yield and their contributing traits and nutrient uptake in grain and stover/straw of crops. Further, atleast one more year research is needed to develop the module for maize+mun/urdbean intercropping system.